Staphylococcus Aureus and its importance in the context of nosocomial infections: literature review (Research, Society and Development, 2022)
Staphylococcus aureus make up the human microbiota, being found mainly on the skin and in the nasal cavities, favoring contact contamination, which makes it a problem when it comes to hospital infections. The objective of this review was to verify the relationship between the S. aureus bacteria and hospital infections through searches on digital platforms such as Scielo, Google Scholar and Medline, seeking articles, books and public journals on the subject. It was possible to verify the importance of S. aureus in hospitals, noting that the patients most susceptible to acquiring these infections are patients hospitalized in ICUs for a longer time, or patients who use several antibiotics at the same time, as well as their resistance to several antibiotics. such as Clindamycin, Erythromycin, Gentamicin, Oxacillin, Tetracycline among others. Knowing that S. aureus is found mainly on the hands of health professionals, we propose that simple attitudes such as hand washing and decolonization of the nasal mucosa are important attitudes to avoid transmission.